2011
DOI: 10.1186/1757-7241-19-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a university hospital trauma team activation protocol

Abstract: BackgroundAdmission with a multidisciplinary trauma team may be vital for the severely injured patient, as this facilitates rapid diagnosis and treatment. On the other hand, patients with minor injuries do not need the trauma team for adequate care. Correct triage is important for optimal resource utilization. The aim of the study was to evaluate our criteria for activating the trauma team, and identify suboptimal criteria that might be changed in the interest of precision.MethodsThe study is an observational,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
1
33
0
1
Order By: Relevance
“…The study descriptives, patient demographics and main findings are reported in Table 1. A further two publications were found from Norway and Ireland [23, 24]. Upon author contact, we were informed that 5 resuscitative emergency thoracotomies were performed, with no survivors in Tromsø, Norway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study descriptives, patient demographics and main findings are reported in Table 1. A further two publications were found from Norway and Ireland [23, 24]. Upon author contact, we were informed that 5 resuscitative emergency thoracotomies were performed, with no survivors in Tromsø, Norway.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, of the 70 ETs, 16 were for cardiac injury, of which only 5 survived (32 %) [33]. In a study from Northern Norway ( n  = 142) [23], <3 % of all patients required hemostatic surgery on admission, and only 5 patients had an emergency thoracotomy, with no survivors. In another study from Dublin [24], 5 % of penetrating trauma victims had a thoracotomy, although no further data was provided on indication nor on outcome in this report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is no surprise, thus, that several studies in Scandinavia reports an overtriage of up to 70%, and even as high as 90% in some centres . The MOI criteria have in the same studies been shown to be responsible for a large part of the overtriage, while physiological criteria are the most accurate criteria for identifying seriously injured patients.…”
mentioning
confidence: 95%
“…6 They can also be used for clinical decision making when the trauma patient has just arrived at the emergency room (ER). 7,8 Trauma is a time-sensitive condition and well recognized as one of the main challenges in modern health care. [1][2][3][4] Easy-to-use trauma scoring systems inform physicians of the severity of the trauma in patients and help them to decide the course of trauma management.…”
mentioning
confidence: 99%